2014
DOI: 10.3109/19401736.2014.984164
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny based on two mtDNA genes ( Co-1, Cyt-B ) among Sculpins (Scorpaeniformes, Cottidae) and some other scorpionfish in the Russian Far East

Abstract: The average scores of p-distances at Co-1 and Cyt-b genes revealed a pattern of increased nucleotide diversity for four categories: (1) intraspecies, (2) intragenus, (3) intrafamily, and (4) intraorder. Scores for Co-1 genes were following: (1) 0.24 ± 0.19% (n = 66), (2) 1.54 ± 0.27% (n = 33), (3) 11.57 ± 0.24% (n = 42), and (4) 12.91 ± 0.16% (n = 102); while for Cyt-b genes, those values were (1) 1.92 ± 0.55% (n = 24), (2) 8.19 ± 0.09% (n = 812), (3) 15.42 ± 0.07% (n = 1573), and (4) 23.13 ± 0.19% (n = 211). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 47 publications
6
8
0
Order By: Relevance
“…However, the present genetic data does not support the synonymization of Megalocottus and Myoxocephalus , as was proposed by a number of authors (e.g., [ 10 , 11 , 69 , 70 , 71 ]). The genetic distance between them is significantly larger than the average interspecific distance within the genus Myoxocephalus (see above) and fits into the range of intergeneric distances detected for sculpin fishes [ 16 , 17 , 18 ], nevertheless, having the lowest values (see also the Results section). Instead, our genetic data indicate that the composition of the genera Myoxocephalus and Megalocottus needs revision.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…However, the present genetic data does not support the synonymization of Megalocottus and Myoxocephalus , as was proposed by a number of authors (e.g., [ 10 , 11 , 69 , 70 , 71 ]). The genetic distance between them is significantly larger than the average interspecific distance within the genus Myoxocephalus (see above) and fits into the range of intergeneric distances detected for sculpin fishes [ 16 , 17 , 18 ], nevertheless, having the lowest values (see also the Results section). Instead, our genetic data indicate that the composition of the genera Myoxocephalus and Megalocottus needs revision.…”
Section: Discussionsupporting
confidence: 69%
“…The level of divergence (Dxy = 0.0314 ± 0.0012) between the sequences within this group is slightly higher, but still matches the value of divergence for different species within the same genus (intrageneric level). The level of divergence between clusters 1 and 2 is significantly higher (Dxy = 0.0789 ± 0.0016), matching the values of divergence, albeit the lowest ones, between different genera within the family Cottidae (intrafamily level) [16][17][18]. Comparable values of divergence based on complete mt genomes have been obtained in the pairwise comparisons between the other genera of the cottids studied (Figure 1) such as Megalocottus-Microcottus (Dxy = 0.0829 ± 0.0024), Myoxocephalus-Microcottus (Dxy = 0.0865 ± 0.0015), Myoxocephalus-Enophrys (Dxy = 0.0898 ± 0.0025), Myoxocephalus-Argyrocottus (Dxy = 0.0910 ± 0.0020), Megalocottus-Enophrys (Dxy = 0.0970 ± 0.0023), Megalocottus-Argyrocottus (Dxy = 0.0987 ± 0.0019), Myoxocephalus-Icelus (Dxy = 0.1025 ± 0.0023), and Myoxocephalus-Porocottus (Dxy = 0.1032 ± 0.0021).…”
Section: Complete Mitochondrial Genomessupporting
confidence: 61%
See 1 more Smart Citation
“…Scorpions exhibited the highest percentage of guanine in the COI barcode. Despite this being the first time, to the best of the authors' knowledge, that this issue in scorpions has been reported, some reports in other animal groups identified this type of deviation as a reflection of separate divergence of these groups from their ancestors and sister groups [50][51][52]. More future work is expected to ensue from this finding in order to assess the taxonomic significance of this guanine-skewed composition of COI barcode region in scorpions among all arachnid taxa.…”
Section: Discussionmentioning
confidence: 83%
“…Studies by those of Kartavtsev and Lee (2006); Kartavtsev et al (2007); Kartavtsev et al (2009); Kartavtsev (2011); Kartavtsev et al (2014) reported that the range of sequence divergences values of COI gene between P. cf. binotatus Gunung Tujuh and other Sumatra P. cf.…”
Section: Resultsmentioning
confidence: 99%